Verification of the factorial structure, invariance, and differences in the parental self-efficacy scale in separated parents (Research, Society and Development, 2021)
The socioemotional impact on the separation of a couple is also experienced by their children, who, many of them develop a great dependence because of the separation. In researching this audience, psychometric measurement instruments are lacking to assess constructs of parents separated from their children, so that professionals in the field can use. In this article, we intend to verify the quality of the factorial structure, invariance and differences in parents separated from the construct of parental self-efficacy. The sample consisted of 200 subjects, being 107 mothers and 93 fathers, aged 21 to 40 years; all were divorced and / or separated and had children aged 0 to 3 years. All residents of the State of Bahia. Participants answered questions on the parental self-efficacy scale. Descriptive and inferential statistics and confirmatory analysis were performed. It was observed that in the discriminative analysis, as in content representativeness, all items were significant, confirming the theoretical content-domain relationship of the scale. In the confirmatory factor analysis, the psychometric indicators were in the statistical parameter that indicates the quality of the scale's factorial structure and its reliability indices revealed the consistency of the factorial organization, with seven factors, interrelated. The Teaching and Empathic Responsiveness dimension had the highest scores. The results revealed that the Mother had higher scores compared to the Father. In general, it is noteworthy that the self-efficacy scale is consistent in a sample of separate parents. It is concluded that the parental self-efficacy scale can be administered to separate mothers and fathers to seek guidance with a better emotional organization towards their children.